Key Aspects Of Speech Therapy For Voice Restoration In Cases Of Vocal Cord Dysfunction And Failure - Shaboyan, Mery; Sahakyan, Tamara
This article investigates the underlying causes of vocal fold and hypo dissolution and their pathological impact on the acoustic properties of the voice and respiratory function. It delineates the characteristic symptoms experienced by individuals with vocal fold dysfunction, highlighting the adverse effects on voice quality and communication challenges. It addresses complications associated with vocal fold dysfunction and outlines a structured speech therapy approach to mitigate voice disorders. The therapeutic approach emphasizes integrating interdisciplinary techniques to achieve optimal corrective outcomes. Given its relevance, this issue holds significant importance in both healthcare and pedagogical contexts, particularly in treating and rehabilitating individuals with vocal fold dysfunction.
Keywords: Speech therapy